Biophotonic technologies for assessment of breast tumor surgical margins—A review - Balasundaram, Ghayathri; Krafft, Christoph; Zhang, Ruochong; Dev, Kapil; Bi, Renzhe; Moothanchery, Mohesh; Popp, Juwrgen; Olivo, Malini (Journal of Biophotonics, 2021)
Breast conserving surgery (BCS) offering similar surgical outcomes as mastectomy while retaining breast cosmesis is becoming increasingly popular for the management of early stage breast cancers. However, its association with reoperation rates of 20% to 40% following incomplete tumor removal warrants the need for a fast and accurate intraoperative surgical margin assessment tool that offers cellular, structural and molecular information of the whole specimen surface to a clinically relevant depth. Biophotonic technologies are evolving to qualify as such an intraoperative tool for clinical assessment of breast cancer surgical margins at the microscopic and macroscopic scale. Herein, we review the current research in the application of biophotonic technologies such as photoacoustic imaging, Raman spectroscopy, multimodal multiphoton imaging, diffuse optical imaging and fluorescence imaging using medically approved dyes for breast cancer detection and/or tumor subtype differentiation toward intraoperative assessment of surgical margins in BCS specimens, and possible challenges in their route to clinical translation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: biophotonic; breast cancer; breast conserving surgery; imaging; intraoperative; photoacoustic; Raman spectroscopy; tumor margin